Samotny orzel - Steel, Danielle; Andrzejewska, Maria Karolina (Katowice : Ksiaznica, 2001)
Polish translation of "Lone Eagle". A love story which begins in 1940. Joe and Kate meet and their love grows over the decades.
Keywords: Aeronautical engineers -- Fiction; Air pilots -- Fiction